Prevalence of overweight / obesity among school children in Karnataka, South India - Baby S Nayak (Universiti Kebangsaan Malaysia, 2011)
Worldwide, non-communicable diseases (NCD) represent 43% of the burden of disease and are expected to be responsible for 60% of the disease burden and 73% of all deaths by 2020.Obesity in children and adolescents is gradually becoming a major public health problem in many developing countries, including India. The present study was undertaken to identify the prevalence of childhood overweight /obesity and to find the relationship between BMI and waist circumference of the children. Eleven schools were selected randomly from Udupi district of Karnataka state, India. A school based survey was carried out among 2938 school children in the age group of 10 – 16 years. On the day of survey, the purpose of the study was explained. The demographic proforma was administered and standard procedures were followed to assess the anthropometric measurements. Result showed that 7% of children were overweight and 5% were obese. The Pearson Correlation computed between BMI and waist circumference showed a positive ( r = 0.763, p =<0.0001) relationship between BMI and waist circumference. The study concluded that childhood obesity prevalence is increasing among children. Higher BMI was found among children in the age of 10 – 12 years and among girls than the boys. The gender difference in BMI could be due to sedentary lifestyles of girls. As the BMI of children increases the waist circumference also increases.